Vascular Guidance: Microstructural Scaffold Patterning for Inductive Neovascularization - Daniel Muller; Harvey Chim; Augustinus Bader; Matthew Whiteman; Jan-Thorsten Schantz (Stem Cells International)
Current tissue engineering techniques are limited by inadequate vascularisation and perfusion of cell-scaffold constructs. Microstructural patterning through biomimetic vascular channels within a polymer scaffold might induce neovascularization, allowing fabrication of large engineered constructs. The network of vascular channels within a frontal-parietal defect in a patient, originating from the anterior branch of the middle meningeal artery, was modeled using computer-aided design (CAD) techniques and subsequently incorporated into polycaprolactone (PCL) scaffolds fabricated using fused deposition modeling (FDM). Bone marrow-derived mesenchymal stem cells (MSCs) were seeded onto the scaffolds and implanted into a rat model, with an arteriovenous bundle inserted at the proximal extent of the vascular network. After 3 weeks, scaffolds were elevated as a prefabricated composite tissue-polymer flap and transferred using microsurgical technique. Histological examination of explanted scaffolds revealed vascular ingrowth along patterned channels, with abundant capillary and connective tissue formation throughout experimental scaffolds, while control scaffolds showed only granulation tissue. All prefabricated constructs transferred as free flaps survived and were viable. We term this concept “vascular guidance,” whereby neovascularization is guided through customized channels in a scaffold. Our technique might potentially allow fabrication of much larger tissue-engineered constructs than current technologies allow, as well as allowing tailored construct fabrication with a patient-specific vessel network based on CT scan data and CAD technology.